Impacts of Anthropogenic Water Withdrawals on the Hydropower Potential of the Ouémé River at the 2040’s Horizon in Benin - NOUNANGNONHOU, Cossi Télesphore; FIFATIN, François-Xavier; ACAKPOVI, Amevi; SANYA, Emile (My University, 2019)
Hydropower is one of the major renewable energy resources worldwide faces challenges day after day. Climate change and anthropogenic pressures can have negative impacts on hydropower production. This paper considers reservoir-dams in the GR2M hydrological model in order to simulate the impacts of anthropogenic water withdrawals on the hydropower potential of the Ouémé River basin (Benin) by 2040. The rain-flow model, GR2M of the National Institute for Research in Science and Technology for Environment and Agriculture (IRSTEA) is used to estimate the impacts of two scenarios of future water withdrawals on the hydropower potential of the Ouémé River. Water withdrawals taken respectively at the Bétérou, Savè and Kétou sites, representing the Ouémé River, using multifunction tanks and mixed tanks were carefully analyzed. The results obtained show that the mixed reservoir scenario is more tolerant to water withdrawals compared to the multi-function reservoir scenario regardless of the site considered. In addition, high sensitivity of the hydropower potential to annual water withdrawals was observed at Bétérou, which was relatively lower at the Savè and Kétou sites. Moreover, with the mixed reservoir scenario, Savè and Kétou sites show stability in their production at water withdrawals rates lesser than 10% and 20% respectively. This study highlights the importance of the Ouémé basin’s potential, the exploration of which would constitute a strong link in the development strategy of energy and hydro-agricultural sectors of Benin Republic.
Keywords: Hydropower; Climate Change; GR2M; Anthropogenic Water Withdrawals; Ouémé River